Original paperTHE RELEVANT USE OF THE TRADITIONAL TUNISIAN GAME ‘‘RAQASSA’’ FOR CARDIOVASCULAR STIMULATION IN SCHOOLCHILDREN - Jebali, T.; Moalla, W.; Elloumi, M.; Padulo, J.; Baquet, G.; Chamari, K. (Biology of Sport, 2013)
The aim of this study was to investigate the heart rate (HR) responses, the rate of perceived exertion (RPE), and the feeling during physical education schooling while performing traditional games activities compared to intermittent exercise. Nineteen pre-pubertal children randomly performed on different days two types of lessons (intermittent running mode vs. traditional Tunisian “Raqassa” game) lasting 12-min each. HR was continuously recorded during both lessons, while ratings of perceived exertion and Feeling values were recorded after the sessions. The mean HR value during the traditional game was significantly higher than during intermittent exercise (p<0.05). Conversely, the perceived exertion score was significantly higher after intermittent exercise than the traditional exercise game (p<0.05), showing that the higher cardiovascular strain of the game was perceived as “lighter” than the run. Simultaneously, the children’s Feeling was significantly higher after the traditional game than intermittent exercise (p<0.001), showing a higher satisfaction from playing with respect to running. Exercise based on the “Raqassa” traditional game could be used in pre-pubertal children as an alternative or as an additional method for suitable cardiovascular stimulation during physical education lessons with lower perceived exertion and better feeling compared to intermittent running.